2010
DOI: 10.1080/00206810903442402
|View full text |Cite
|
Sign up to set email alerts
|

Petrogenesis of peraluminous magmas from the Akum-Bamenda Massif, Pan-African Fold Belt, Cameroon

Abstract: Peraluminous intrusives of the Akum-Bamenda Massif, Pan-African Belt, Central Cameroon, were synkinematically emplaced in a Pan-African sinistral strike-slip shear zone. The rock sequences consist of medium-grained leucogranites, fine-grained leucogranites, and orthogneisses of biotite granite composition; in aggregate, they cover a range from about 65 to 74 wt.% SiO 2 , defining a continuous chemical evolutionary trend and displaying characteristics of the high-K and medium calc-alkaline series. Leucogranites… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 53 publications
1
14
0
Order By: Relevance
“…In the millications R1 versus R2 discrimination diagram ( Figure 13) of [39] used to distinguish the tectonic setting, Bamenda granites plot in the syn-collision field whereas Bamenda leucogranites plot in the post-tectonic field. From the two geotectonic settings proposed by [40] to constrain the generation of high-K and cal-alkaline magma, the syn-to post-collisional settings could be reasonably ascribed to Bamenda granitoids which is consistent regarding their comparison with other works carried out in the eastern part of the central domain of the Pan African Fold Belt in Cameroon [4,5,12,14]. According to [41], the crustal source rocks of high-K magmas in this context may occur as a consequence of decompression following the lithospheric root delamination.…”
Section: Tectonic Setting and Pan-african Fold Belt Evolution In Camesupporting
confidence: 82%
See 3 more Smart Citations
“…In the millications R1 versus R2 discrimination diagram ( Figure 13) of [39] used to distinguish the tectonic setting, Bamenda granites plot in the syn-collision field whereas Bamenda leucogranites plot in the post-tectonic field. From the two geotectonic settings proposed by [40] to constrain the generation of high-K and cal-alkaline magma, the syn-to post-collisional settings could be reasonably ascribed to Bamenda granitoids which is consistent regarding their comparison with other works carried out in the eastern part of the central domain of the Pan African Fold Belt in Cameroon [4,5,12,14]. According to [41], the crustal source rocks of high-K magmas in this context may occur as a consequence of decompression following the lithospheric root delamination.…”
Section: Tectonic Setting and Pan-african Fold Belt Evolution In Camesupporting
confidence: 82%
“…The central domain of the PANEFB consists of an assembly of fragments of Paleoproterozoic continental crust recrystallised under high-grade granulite facies (850-900°C, 10-12Kb) at ca 2100Ma [11] intruded by widespread Neoproterozoic plutonic rocks of high-K, calc-alkaline affinities [12,13,14,15,16]. [5] in Akum area located south of the study area have distinguished a rock sequence consisting of peraluminous S-type leucogranites and orthogneissified I-type biotite granite ( Figure 1b); all displaying characteristics of medium to high-K calc-alkaline series.…”
Section: Geological Settingmentioning
confidence: 99%
See 2 more Smart Citations
“…The scholar indicated that Bamenda belongs to the West Cameroon Highlands, the most important geomorphologic system in the region. The study area constitutes part of the Bamenda Mountains which is made up of a basement rock comprised mainly of leucogranite of Precambrian age, with the basement rock overlain by volcanic materials composed of mafic and felsic lavas [11]. The mafic lavas comprise of basalts which outcrop as lava flows and pyroclastic deposits, while the felsic lavas include trachytes, phonolites, and rhyolites [12].…”
Section: Geology and Hydrogeology Of The Study Areamentioning
confidence: 99%